STRATEGIES FOR ENHANCING TRANSLATION ENVIRONMENT - Saliyeva Zarrina Ilxomovna; Abdullayeva Sarvinoz Qakhramonovna (American Journals Publishing, 2024)
Improving the translation environment is very important in today's globalization. Translation is not only about changing one language into another, but also plays an important role in the process of intercultural communication, information dissemination and knowledge exchange. Several strategies need to be developed and implemented to improve the translation environment.
Keywords: Translation, linguistics, terminology, programs, seminars, modern translation problems, intercultural communication.